Prospective Risk Assessment of some Heavy Metals on Tilapia zilli in Temsah Lake - Elsharkasy, Amira M.H.; Ahmed, Amal A.M.; Ismail, Mona M.; Elsheshtawy, Hassnaa M.; Hassan, Marwa A. (Journal of Advanced Veterinary Research, 2024)
This study was conducted to determine the pollution index of some heavy metals in Temsah Lake water to assess their transfer into Tilapia zillii tissues using bioaccumulation factors as well as evaluate their associated health risks. Results showed that Pb, Cd, and Cu levels increased significantly during spring, summer, and both spring and summer, respectively. The pollution index of heavy metals in the Temsah Lake revealed that Fe had a moderate effect in winter and a strong effect in the other seasons. Pb had a serious impact on aquatic life in the spring and autumn, while Cd had a serious impact in the summer and autumn. Water temperature is strongly correlated with Cu in the liver, Pb in the musculature, and Cd in the water and liver. Conversely, it negatively correlated with fish weight, length, Fe, Zn, and Cu in the musculature. Fish length showed an inverse relationship with water Cu, Cd, Pb, and Cd. The histopathological examination revealed hydropic degeneration, fatty changes, and interstitial and focal infiltration of immunocompetent cells. Muscular tissue revealed degenerative changes manifested by atrophy and fragmentation of muscular fibers in some specimens. The bioaccumulation factor of heavy metals in Tilapia zilli musculature and liver was found to be highest during winter. Fish musculature was safe for Pb, Cd, and Cu and might represent potential risks for Fe and Zn. In conclusion, warm seasons have the highest integrated biomarker response (IBRv2) scores for the detected heavy metals, also the sum of IBRv2 of the heavy metals content is the highest in musculature followed by livers then water samples. Herein, TCR results for Pb and Cd in Tilapia zilli are within the permissible range (10âˆ’4 to 10âˆ’6).